Female Genital Mutilation/Cutting in Children and Adolescents Illustrated Guide to Diagnose, Assess, Inform and Report - Abdulcadir, Jasmine; Sachs Guedj, Noémie; Yaron, Michal (Springer International Publishing : Imprint: Springer, 2022)
This open access illustrated guide focuses on Female Genital Mutilation/Cutting (FGM/C) in children and adolescents. FGM/C comprises all procedures that involve partial or total removal of the external female genitalia or injury to the female genital organs for nonmedical reasons. It is mainly carried out during childhood, before the age of 15. The signs of FGM/C can be subtle, and the examiner must be trained with a wide range of normal genitalia both before and after puberty, FGM/C types and subtypes, complications and differential diagnosis. This volume is a reference containing iconographic material of both pre and post pubertal genitals with and without genital cutting. This book will guide health care professionals in making the correct diagnosis, outline the clinical management, enhance patient-provider communication, and will enable accurate recording and reporting to governments where required. .